Validation of four different risk stratification systems in patients undergoing off-pump coronary artery bypass surgery: a UK multicentre analysis of 2223 patients. Issue 4 (1st April 2003) - Al-Ruzzeh, S; Asimakopoulos, G; Ambler, G; Omar, R; Hasan, R; Fabri, B; El-Gamel, A; DeSouza, A; Zamvar, V; Griffin, S; Keenan, D; Trivedi, U; et al.
Abstract : Background: Various risk stratification systems have been developed in coronary artery bypass graft surgery (CABG), based mainly on patients undergoing procedures with cardiopulmonary bypass. Objective: To assess the validity and applicability of the Parsonnet score, the EuroSCORE, the American College of Cardiology/American Heart Association (ACC/AHA) system, and the UK CABG Bayes model in patients undergoing off-pump coronary artery bypass surgery (OPCAB) in the UK. Methods: Data on 2223 patients who underwent OPCAB in eight cardiac surgical centres were collected. Predicted mortality risk scores were calculated using the four systems and compared with observed mortality. Calibration was assessed by the Hosmer–Lemeshow (HL) test. Discrimination was assessed using the receiver operating characteristic (ROC) curve area. Results: 30 of 2223 patients (1.3%) died in hospital. For the Parsonnet score the HL test was significant (p < 0.001) and the receiver operating characteristic curve (ROC) area was 0.74. For the EuroSCORE the HL test was also significant (p = 0.008) and the ROC area was 0.75. For the ACC/AHA system the HL test was non-significant (p = 0.7) and the ROC area was 0.75. For the UK CABG Bayes model the HL test was also non-significant (p = 0.3) and the ROC area was 0.81. Conclusions: The UK CABG Bayes model is reasonably well calibrated and provides good discrimination when applied to OPCAB patients in the UK. Among the other three systems, the ACC/AHA system is well calibrated but its discrimination power was less than for the UK CABG Bayes model. These data suggest that the UK CABG Bayes model could be an appropriate risk stratification system to use for patients undergoing OPCAB in the UK.